Evaluasi Sistem Perizinan Lingkungan Hidup Dan Dampaknya Terhadap Perlindungan Lingkungan di Kota Makassar - Ambo Masse; Khaeriyah Khaeriyah; Nurasia Natsir (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
The environmental licensing system is an important instrument in environmental protection. However, its implementation in Makassar City has not been optimal yet. This study aims to evaluate the environmental licensing system and analyze its impact on environmental protection in Makassar City. The research method used is descriptive qualitative, with data collection through interviews, observations, and document studies. The results show that the environmental licensing system in Makassar City has not been effective. There are several problems, such as convoluted procedures, lack of coordination between related agencies, as well as weak supervision and law enforcement. The impact of an ineffective environmental licensing system is the high level of pollution and environmental degradation in Makassar City. Some examples of cases found include the disposal of industrial waste into water bodies, deforestation of protected forests, and development that does not pay attention to environmental sustainability. To improve the effectiveness of the environmental licensing system and its impact on environmental protection, efforts are needed, such as simplifying procedures, enhancing coordination between agencies, strengthening human resource capacity, and imposing strict sanctions on violators.